Metode Lowest Supply Lowest Cost (LSLC) Pada Masalah Transportasi Tidak Seimbang (Studi Kasus Pada Ditribusi Air Minum PT. Anugerah Berkah Bersaudara) - Amellia Fadjri; Defri Ahmad (Journal of Mathematics UNP, 2022)
Distribution of goods is very important for the company. In order to get a bigger profit, the company tries to deliver the goods in the most effective way possible. There are several warehouse locations and several destinations, with different shipping costs, so the distribution problem can be solved using transportation methods. There are many methods that can be used to determine the optimal solution to the transportation problem. In this study, the Lowest Supply Lowest Cost (LSLC) method was used to determine the initial solution and the Stepping Stone method was used to determine the optimal solution for the distribution of Bottled Drinking Water at PT. Anugerah Berkah Brothers, with the aim of minimizing transportation costs. Distribution problems at PT. Anugerah Berkah Brothers is an unbalanced transportation problem, because the amount of inventory is greater than the amount of demand. Based on the results of the discussion obtained that PT. Anugerah Berkah brothers can save transportation costs from before as much as 8% of the initial cost.